2018
DOI: 10.7717/peerj.4654
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic structuring at the northern limits of the Australian smelt (Retropinna semoni) cryptic species complex

Abstract: Freshwater fishes often exhibit high genetic population structure due to the prevalence of dispersal barriers (e.g., waterfalls) whereas population structure in diadromous fishes tends to be weaker and driven by natal homing behaviour and/or isolation by distance. The Australian smelt (Retropinnidae: Retropinna semoni) is a native fish with a broad distribution spanning inland and coastal drainages of south-eastern Australia. Previous studies have demonstrated variability in population genetic structure and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…Consistent with this prediction, a microsatellite study of the same populations as reported on here, showed very high levels of genetic differentiation (Islam, Schmidt, Crook, & Hughes, 2018) for both lineages.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with this prediction, a microsatellite study of the same populations as reported on here, showed very high levels of genetic differentiation (Islam, Schmidt, Crook, & Hughes, 2018) for both lineages.…”
Section: Discussionsupporting
confidence: 89%
“…If dispersal was strongly limited for extended periods, some genetic differentiation would be expected due to the effects of genetic drift, different selection pressure or both. However, no significant pairwise F ST values between upstream and downstream sites of two of those three rivers (Logan and Nerang River) with low variation within Brisbane River were reported from genetic analysis of these same sites (Islam et al, 2018),…”
Section: Discussionmentioning
confidence: 89%
“…In particular we've demonstrated the util- catchments. These include crustaceans (Bentley, Schmidt, & Hughes, 2010;Sharma & Hughes, 2009), fishes (Bishop, Hughes, & Schmidt, 2018;Hughes et al, 2015;Islam, Schmidt, Crook, & Hughes, 2018) and a turtle endemic to the Mary River (Schmidt, Espinoza, Connell, & Hughes, 2018). Together these findings highlight the significance of Tinana Creek as an important reservoir of intraspecific diversity in Mary River cod and numerous other freshwater taxa.…”
Section: Discussionmentioning
confidence: 84%